The Kingfisher treasury of princess stories - Aggs, Patrice; Waters, Fiona (London : Kingfisher, 2008)
A collection of thirteen folklore and fiction stories about all types of princesses, including selections from Joan Aiken, Lloyd Alexander, Hans Christian Andersen, and Vivian French.
5.5
3-6
Keywords: Fairy tales; Princesses -- Literary collections